2021
DOI: 10.2147/jir.s293825
|View full text |Cite
|
Sign up to set email alerts
|

Association of a High Neutrophil-to-Lymphocyte Ratio with Hyperdense Artery Sign and Unfavorable Short-Term Outcomes in Patients with Acute Ischemic Stroke

Abstract: Purpose Immune–inflammatory processes are involved in all the stages of stroke. This study investigated the association of the neutrophil-to-lymphocyte ratio (NLR) with the hyperdense artery sign (HAS) observed on brain computed tomography (CT) and with clinical features in patients with acute ischemic stroke. Methods We retrospectively enrolled 2903 inpatients with acute ischemic stroke from May 2010 to May 2019. Data collected included imaging studies, risk factors, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
(22 reference statements)
4
17
2
Order By: Relevance
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…26 Reports have demonstrated that the immune-inflammatory markers increase linearly with the initial NIHSS and the discharge mRS scores. 7,14 We obtained the same results among patients with OHIS. Large-artery atherosclerosis and cardioembolism, which usually cause higher stroke severity with higher NIHSS scores, account for more than threequarters of IHIS cases.…”
Section: Discussionsupporting
confidence: 71%
“…9 Several immune-inflammatory markers, such as the neutrophil counts (NC), platelet-to-lymphocyte ratio (PLR), neutrophil-tolymphocyte ratio (NLR), and systemic immune-inflammation index (SII), have been reported to be associated with poor outcomes among patients with acute stroke, cardiovascular disease, and various types of cancer. 7,[10][11][12][13][14] However, alterations in immune-inflammatory markers have rarely been described in patients with IHIS. In this study, we investigated the differences of clinical features, four immune-inflammatory markers (NC, PLR, NLR, and SII), and the outcomes between patients with IHIS and those with OHIS.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Acute ischemic stroke patients show an elevated ratio of neutrophils to lymphocytes and worse prognosis. 30 T cells are involved in the late phase of cerebral ischemia, and different T cell subtypes play different roles in ischemic stroke. 31 Our results link down-regulation of resting mast cells with greater risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%